The mechanism of the photochromic transformation of spirorhodamines - Montenegro, Hugo Orlando (2012)
We investigate the equilibrium, kinetics, and mechanism of the photochromic transformation of a series of amido spirorhodamine compounds—differing in the nature of the substituents of the amido group and in the rhodamine chromophore—in ethanol at room temperature in the presence of trifluoroacetic acid. A proton participates in the equilibrium between the spiro form and the open rhodamine form. The relaxation times in the dark or under continuous irradiation show a linear dependence on the proton concentration. The slopes of these plots show a linear free energy relation with the equilibrium constant of the transformation. A mechanism involving reversible reaction steps between four states: the two thermodynamically stable isomers, a protonated spiro form, and a deprotonated open form, can account for the kinetic observations in the dark and under irradiation.